2022
DOI: 10.1088/1361-6668/ac68a5
|View full text |Cite
|
Sign up to set email alerts
|

Roles of electron mean free path and flux pinning in optimizing the critical current in YBCO superconductors

Abstract: We present a way to reach the maximum possible critical current density, Jc , for YBa2Cu3O6+x (YBCO) thin films. This value is found to be around ten times the currently reached values. It is found that the Jc}(0 T) is governed by the mean free path of the electrons, as is the critical temperature, Tc . The Jc in field, on the other hand, is governed by flux pinning and can be enhanced by optimizing the size and distribution of the non-superconducting nanoinclusions. By optimizing both the mean free path and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…The remarkable agreement of the deduced value, , and the value reported in the original work on MATBG by Cao et al [ 95 ], , which was calculated based on normal state charge carriers density in MATBG, independently validates our primary idea [ 84 ] about the fundamental nature of the self-field critical current in weak-links samples [ 84 , 85 , 111 ]. This concept was recently proven by Paturi and Huhtinen [ 112 ], who utilized the fact that the London penetration depth, , in real samples, depends on the mean free-path of charge carriers, : where is the effective penetration depth, and is the penetration depth in samples, exhibiting a very long mean free-path, . Paturi and Huhtinen [ 112 ] varied in YBa 2 Cu 3 O 7-x films and showed that the change in satisfies Equations (18) and (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable agreement of the deduced value, , and the value reported in the original work on MATBG by Cao et al [ 95 ], , which was calculated based on normal state charge carriers density in MATBG, independently validates our primary idea [ 84 ] about the fundamental nature of the self-field critical current in weak-links samples [ 84 , 85 , 111 ]. This concept was recently proven by Paturi and Huhtinen [ 112 ], who utilized the fact that the London penetration depth, , in real samples, depends on the mean free-path of charge carriers, : where is the effective penetration depth, and is the penetration depth in samples, exhibiting a very long mean free-path, . Paturi and Huhtinen [ 112 ] varied in YBa 2 Cu 3 O 7-x films and showed that the change in satisfies Equations (18) and (19).…”
Section: Discussionmentioning
confidence: 99%
“…This concept was recently proven by Paturi and Huhtinen [ 112 ], who utilized the fact that the London penetration depth, , in real samples, depends on the mean free-path of charge carriers, : where is the effective penetration depth, and is the penetration depth in samples, exhibiting a very long mean free-path, . Paturi and Huhtinen [ 112 ] varied in YBa 2 Cu 3 O 7-x films and showed that the change in satisfies Equations (18) and (19).…”
Section: Discussionmentioning
confidence: 99%
“…High-temperature superconductor YBa 2 Cu 3 O 6+x (YBCO) thin films and coated conductors hold great potential for a variety of power applications, energy storage, high-speed computing etc [1][2][3][4][5], but to realize their full capability, the overall critical current density (J c ) needs to be maximized [6,7]. Since the thermal excitation of Cooper pairs and the field strength dependent Meissner effect greatly affect the J c , it is essential to design specific structures for various applications operating at different temperatures and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…T O maximize the absolute critical current density J c of YBCO thin films and coated conductors at high magnetic fields favourable for electric power applications [1]- [7], requirements of both the high crystalline quality and optimal flux pinning properties should be fulfilled [8]- [10]. The flux pinning structure organized with an artificially produced nanocolumn network within the YBCO matrix that maximally pins the vortices is widely studied [11]- [17], but the formation of crystalline defects that directly affect the shortening of the electron mean free path and thus the zero-field critical current density has got less attention in the field of hightemperature superconductors [9], [18]- [21]. In the zero-and low-field applications below ≈100 mT, the crystalline structure of YBCO is solely responsible for maximum J c and in the mid-field applications between 100 mT and ≈2 T, the J c at the zero-field unambiguously limits the in-field properties [10].…”
Section: Introductionmentioning
confidence: 99%